ALTERNATIVE ENERGY SOURCES (American Journal of Technology and Applied Sciences, 2023)
renewable energy is a hot topic nowadays. With the ever-growing number of populations, demand of energy is also increasing every day. Non-renewable sources are limited, not environment friendly and increase or decrease in production of these sources can have direct result on the inflation. It is hard to live without Energy, but it is impossible to find another planet to live in. The use of renewable energy has many potential benefits, including human beings and environment. Comparative analysis of resources and reasons why we should use more alternative resources than fossil fuels are provided in the article.